2005
DOI: 10.1021/cg0497546
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of PbCrO4 and Pb2CrO5 Rods via a Microwave-Assisted Ionic Liquid Method

Abstract: Lead chromate (PbCrO 4 ) rods and dilead pentaoxochromate (Pb 2 CrO 5 ) with bundle-like and rod-like morphologies have been successfully synthesized by a simple microwave-assisted ionic liquid method. In the presence of NaOH, single-crystalline Pb 2 CrO 5 bundles and rods could be synthesized by microwave heating a solution containing lead acetate and potassium dichromate at 90 °C for 10 min. However, single-crystalline PbCrO 4 rods could be prepared by microwave heating at 50 °C for 10 min without using NaOH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 23 publications
(36 reference statements)
1
29
0
1
Order By: Relevance
“…As seen in Figure 2F, the surface of the nanorod became rough after exposure to electron beam irradiation. Similar cases of one-dimensional structures changing their morphology under electron beam irradiation have been reported in; for example, PbCrO 4 rods, 57 Ag 6 Mo 10 O 33 rods, 58 and Bi nanotubes, 59 etc. The crystal phase and molecular structure of the typical sample were characterized by XRD and FTIR.…”
Section: Resultssupporting
confidence: 79%
“…As seen in Figure 2F, the surface of the nanorod became rough after exposure to electron beam irradiation. Similar cases of one-dimensional structures changing their morphology under electron beam irradiation have been reported in; for example, PbCrO 4 rods, 57 Ag 6 Mo 10 O 33 rods, 58 and Bi nanotubes, 59 etc. The crystal phase and molecular structure of the typical sample were characterized by XRD and FTIR.…”
Section: Resultssupporting
confidence: 79%
“…As shown in figure 2a, a typical TEM image of S1 clearly revealed a rod-like morphology with a diameter in the range of 240-970 nm, a length in the range of 6.9-17 µm. Typical morphologies of the Pb 2 CrO 5 products in [14] were rods with lengths of about 2 to 13 µm and diameters of about 500 nm. In comparison with [14], the products here had a wide range of lengths and diameters.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous work, some methods have been employed to synthesize PbCrO 4 nanorods [13,14], but there has been scarcely study on the synthesis of Pb 2 CrO 5 nanorods [14] until now. As is well known, the properties of nanomaterials are highly size-and shape-dependent [15].…”
Section: Introductionmentioning
confidence: 99%
“…Lately, by combining the advantages of both room temperature ionic liquids and microwave heating, a new microwave-assisted ionic liquid method has developed for fast controlled synthesis of nanorods and nanowires of Te and ZnO (Jiang & Zhu, 2005). Zhu and coworkers ) synthesized single-crystal tellurium nanowires using microwave heating in n-butylpyridinium tetrafluoroborate ionic liquid in the presence of polymer surfactant of poly (vinylpyrrolidone) (Wang & Zhu, 2005, Jiang et al, 2006, Singh et al, 2008, Liu et al, 2006. Single-crystalline Bi 2 S 3 and Sb 2 S 3 nanorods have been synthesized using the microwaveassisted ionic liquid method by Jiang and Zhu (Jiang & Zhu, 2005 The morphologies of the samples were investigated by transmission electron microscopy (TEM).…”
Section: Microwave Heating Synthesismentioning
confidence: 99%
“…So far only a handful of studies have reported on the fabrications of nano-or micro-scaled materials including particles of metal oxide (Ding et al, 2007, Bühler & Fledmann, 2006 and sulfide , Jiang & Zhu, 2005. Many metal nanoparticles (NPs) such as Ir (Bühler & Fledmann, 2006), Rh (Wang & Zhu, 2005), Ru , Te (Jiang &. Zhu, 2005), Al (Mu, et al, 2004), Ag , Pt (Foneca et al, 2003), and Au (Dupont et al, 2002) have been prepared in the presence of ionic liquids.…”
Section: Introductionmentioning
confidence: 99%